The Effectiveness of Behavioral Counseling Theory with Modeling Tecniques to Improve The Character Able to Independent Through Lesson Study - Irda Laila; I Ketut Dharsana; Ni Ketut Suarni (RedwhitePress)
This study aims to determine the effectiveness of behavioral counseling modeling techniques to improve the character able to independent characters through lesson. This research is a quasi research (